Manajement Muskuloskeletal Physiotherapy pada Remaja Dengan Gangguan Shin Splint Pada Club Phisical Gunners - Ririn Andasari; Pandu Dwi Panulat; Ayu Rizki Prabaningtyas; Muhammad Faizal Putra; Muhammad Imam (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Medial tibial stress syndrome (MTSS), widely recognized as shin splint, is a prevalent musculoskeletal disorder among adolescent runners. This condition often arises due to excessive training loads, repetitive high-impact activity, poor running mechanics, and the use of footwear that does not provide adequate support. If left unaddressed, shin splints can progress into more severe injuries, potentially limiting physical performance and increasing recovery time. This community service program was conducted with the aim of identifying early signs and providing appropriate management for shin splint complaints in members of the Physical Gunners Running Club. A musculoskeletal physiotherapy approach was applied, integrating multiple strategies: health education sessions to raise awareness of injury mechanisms and prevention, lower limb strengthening exercises to improve muscle endurance and stability, functional assessments using the Hop Test to detect potential symptoms, and personalized discussions and consultations to address individual needs. A total of 33 participants took part in the program. Assessment results revealed that 17 individuals (54.8%) presented positive Hop Test outcomes, indicating the presence of shin splint symptoms. These findings underscore the importance of early screening and prompt intervention, especially for physically active adolescents engaged in repetitive running activities. The implementation of this program demonstrated that physiotherapy interventions combining structured educational content and tailored exercise programs can effectively increase awareness, promote safe training habits, and reduce the risk of injury recurrence. Additionally, the program fostered active participation from the community, encouraging sustainable lifestyle changes. Overall, this activity shows promise as a preventive model that can be adapted and applied to other adolescent running communities, contributing to long-term musculoskeletal health, enhanced performance, and the promotion of healthy and active behavior.